Coupled N and P cycling as driven by microbial taxa and interactions - Jiao, Xinyu; Wei, Yanan; Chen, Yang; Zhang, Chaoyu; Du, Hongmei; Yu, Wenjuan; Kang, Hongzhang (Frontiers in Microbiology, 2026)
The coupled cycling of nitrogen (N) and phosphorus (P) is fundamental to ecosystem functioning, yet the specific microbial taxa and their interactions underlying N-P coupling and decoupling remain poorly understood. Based on a natural laboratory in Yunnan with both coupled and decoupled N-P cycling, we explored bacterial, fungal, and phoD-harboring communities using amplicon sequencing and their relationships with N and P cycling variables. We uncovered 14 phyla and 68 genera both correlated with N and P cycling variables, identified as coupled taxa. Among them, 5 coupled phyla (Nitrospirota, WPS-2, Mortierellomycota, Fungi_phy_Incertae_sedis, and Rozellomycota) and 24 coupled genera (Candidatus Koribacter, Candidatus Solibacter, A21b, etc.) were also enriched in sites where N and P dynamics change synchronously (coupled sites), indicating a key role of these coupled taxa in promoting N-P coupling. The 11 phyla and 48 genera correlated with either N- or P-cycling variables were grouped as decoupled taxa. Moreover, the networks composed of coupled taxa (coupled networks) displayed a greater ratio of positive to negative interactions than those composed of decoupled taxa (decoupled networks). Literature confirms that potential keystone genera (WPS-2, Acidibacter, TK10, etc.) from the coupled network positively interacted with each other to facilitate N-P coupling while potential keystone genera (an unclassified Subgroup_17 genus, etc.) from the decoupled network negatively interact with members to enhance N-P decoupling. These findings suggest that coupled taxa, individually and by synergistically interacting, could enhance N-P coupling whereas decoupled taxa, individually and by antagonistically interacting, might facilitate N-P decoupling. Overall, by uncovering key microbial taxa and interactions underpinning N-P coupling, our study provides a foundation for managing nutrient cycling in forest ecosystems under environmental change.